Novel Authentication Schemes for IoT Based Healthcare Systems - Jia-Li Hou; Kuo-Hui Yeh (International Journal of Distributed Sensor Networks)
With the advancement of information communication technologies, the evolution of the Internet has given rise to a ubiquitous network consisting of interconnected objects (or things), called the Internet of Things (IoT). Recently, the academic community has made great strides in researching and developing security for IoT based applications, focusing, in particular, on healthcare systems based on IoT networks. In this paper, we propose a sensor (or sensor tags) based communication architecture for future IoT based healthcare service systems. A secure single sign-on based authentication scheme and a robust coexistence proof protocol for IoT based healthcare systems are proposed. With the formal security analysis, the robustness of the two proposed schemes is guaranteed under the adversary model.